PENGARUH KUALITAS PRODUK DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN DI CHATIME SOEKARNO HATTA KOTA MALANG - Rahardi Adnan Ardiansyah; Achmad Zaini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this research wa to analyze the effect of product quality and packaging design on purchasing decisions in Chatime Soekarno Hatta Malang City. The reserch is quatitative research. .A data collection technique that distributed questionnaires to 98 respondents,. who were customer of Chatime Soekarno Hatta Malang City. Purposive sampling technique and uses multiple linier regression analysis and hypothesis testing. The result of this research showed that product quality and packaging design have a positive and significant effect partially or simultaneously on purchasing decisions in Chatime Soekarno Hataa Malang City.